Uncovering the Environmental and Social Impacts of Renewable Energy Use in the Halal Industry: Empirical Evidence from Indonesia - Muhamad Shulthoni; Muhammad Khoirul Fikri; Hendri Hermawan Adinugraha (International Journal of Science and Environment (IJSE), 2025)
This research aims to uncover the environmental and social impacts of using renewable energy in the halal industry in Indonesia. Using a case study-based qualitative approach, this research explores the implementation of renewable energy, such as biomass and solar panels, in several companies in West Java, East Java, and West Sumatra. Data collection techniques included in-depth interviews, participatory observation, and document analysis, which were thematically analyzed to identify implementation impacts and challenges. The results show that using renewable energy has reduced greenhouse gas emissions by 30% in the last five years and reduced water and soil pollution by 40%. Socially, the implementation created green jobs, empowered local communities, and improved people’s quality of life through access to clean energy. The study identifies key challenges, such as high initial investment and lack of energy literacy among industry players. This research offers a novel contribution by integrating environmental, social, and Sharia sustainability values in the impact analysis of renewable energy. The practical implications include the need for government incentive policies, workforce training, and multi-sectoral collaboration to support the sustainable transformation of the halal industry in Indonesia.